The effects of rosemary essential oil supplementation on growth performance, rumen flora and antioxidant blood parameters in growing Merino lambs - Cetin, I; Cetin, E; Karakcı, D; Ercetin, E; Bugdayci Kırmızı, O; Yeşilbağ, DY (Journal of the Hellenic Veterinary Medical Society, 2024)
Thirty-two male growing Merino lambs (78 ± 5 days of age) were used in a 45-day randomized complete block desing to determine the effects of rosemary essential oil (REO) on the growth performance, rumen fermentation, rumen protozoa population, plasma antioxidant enzyme parameters and fecal microbiology. The control group was fed a diet consisting of concentrate and alfalfa hay. The lambs in control group did not receive REO whereas each lamb in experimental groups supplemented with 250 mg/d (R250), 500 mg/d (R500) and 750 mg/d (R750) REO throughout the study. There weren’t statistically differences (P>0.05) in average initial weight, average final weight, live weight gain, average daily gain, daily feed intake, daily dry matter intake and feed conversion ratio between the control and experimental groups. There were also no differences (P>0.05) in the rumen pH, fecal pH, NH3N and rumen volatile fatty acid (VFA) profile of the control and experimental groups. At the end of the study, although the plasma superoxide dismutase (SOD) value increased significantly (P<0.05) in the experimental groups (R500 and R750), glutathione peroxidase (GPX) and catalase values did not differ between REO groups and control. In addition, the fecal microorganism profile did not differ statistically (P>0.05) between the control and experimental groups. The results of this study show that the addition of REO to Merino lamb rations is more effective on antioxidant parameters than on performance parameters and can be used as a natural antioxidant product